Impact of Lockdown in the FMCG sector of the Indian Stock Market – Analysis using Statistical Methods - et. al., M. Vivek Prabu, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Covid19 outbreak has shattered the Global economy and Indian economy too had got no exemption from it. Despite the GDP of India moving in the negative trend, very few sectors like Pharmaceutical and FMCG have shown some positive signs because of this pandemic and the lockdown followed by it. Consumer staples will always remain essential irrespective of the economical movement. In particular, during the tougher times, whenever there arises an unprecedented scenario, the humankind will always try to safeguard itself and in turn that will certainly cause a high demand in the FMCG sector. In this paper, we will be analysing the impact of lockdown in the movement of the FMCG sector using some of the Statistical tools